2003
DOI: 10.1016/j.bbmt.2003.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Unrelated umbilical cord blood transplantation in adult patients

Abstract: Since January 1996, we have administered myeloablative therapy followed by infusion of unrelated umbilical cord blood cells in 57 adult patients with high-risk disease. The median age was 31 years (range, 18-58 years), and the median weight was 70 kg (range, 46-110 kg). Two patients were treated for genetic disorders and 55 for advanced hematologic malignancies. The preparative regimens were total body irradiation or busulfan based, both with antithymocyte globulin. HLA matching between donor and recipient was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(92 citation statements)
references
References 26 publications
6
85
1
Order By: Relevance
“…The different genetic background of the transplanted units did not seem to adversely affect the outcome in our patients; our engraftment rate is 93% and our 100-TRM is 15%, conforming to already published data. 1,[3][4][5][6]15,16 In the malignant disorder category, we report in this study an estimated OS and EFS of 41 and 38%, respectively, and others also have reported similar figures. 7,9,15 The degree of HLA disparity seemed to have an effect on the survival of patients with non-malignant hematological disorders, as has been shown by Gluckman et al 3 in Fanconi anemia (FA) patients, although others failed to show such an effect in patients with severe aplastic anemia.…”
Section: Second Transplantssupporting
confidence: 85%
“…The different genetic background of the transplanted units did not seem to adversely affect the outcome in our patients; our engraftment rate is 93% and our 100-TRM is 15%, conforming to already published data. 1,[3][4][5][6]15,16 In the malignant disorder category, we report in this study an estimated OS and EFS of 41 and 38%, respectively, and others also have reported similar figures. 7,9,15 The degree of HLA disparity seemed to have an effect on the survival of patients with non-malignant hematological disorders, as has been shown by Gluckman et al 3 in Fanconi anemia (FA) patients, although others failed to show such an effect in patients with severe aplastic anemia.…”
Section: Second Transplantssupporting
confidence: 85%
“…In a registry-based retrospective study of 682 patients, Rocha et al [13] found both the rate of acute and chronic GvHD in mismatched UCB patients to be lower than the rates in matched BM recipients. However, the relationship between the relatively small cell dose found in UCB units and the delay in engraftment times and subsequent immune reconstitution for neutrophils and platelets continued to be problematic [13,15,17,18]. Long et al [17] noted that infection was the primary cause of death in their study of 57 adults with high-risk disease who were transplanted with unrelated UCB.…”
Section: Transplantation With Ucb : Clinical Studiesmentioning
confidence: 99%
“…However, the relationship between the relatively small cell dose found in UCB units and the delay in engraftment times and subsequent immune reconstitution for neutrophils and platelets continued to be problematic [13,15,17,18]. Long et al [17] noted that infection was the primary cause of death in their study of 57 adults with high-risk disease who were transplanted with unrelated UCB. A large multicenter prospective study of UCB transplantation in adults found that in 34 patients 90% experienced infections; two thirds of those studied reported at least 3 infections during the first 6 months post-transplant [19].…”
Section: Transplantation With Ucb : Clinical Studiesmentioning
confidence: 99%
“…As a result of the early successes with pediatric cord blood transplantation (CBT), cord blood from unrelated donors has been increasingly used as an alternative stem cell source for adult patients with hematological malignancies. [1][2][3][4][5][6][7][8][9][10][11][12][13] Recently several reviews including the clinical results of adult CBT have been published. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] In this review, we focus on recent results of myeloablative CBT in adults.…”
Section: Introductionmentioning
confidence: 99%